Cognitive impairments in patients with rheumatoid arthritis and comorbid anxiety and depressive disorders: Outcomes of the five-years prospective study - A. A. Abramkin; T. A. Lisitsyna; D. Yu. Veltishchev; O. F. Seravina; O. B. Kovalevskaya; S. I. Glukhova; E. L. Nasonov (Научно-практическая ревматология, 2024)
Aim – to assess baseline rates and five-years outcomes of mild cognitive impairments (MCI) in patients with rheumatoid arthritis (RA) and comorbid anxiety and depressive disorders (ADD) receiving conventional synthetic diseasemodifying antirheumatic drugs (csDMARDs) alone or in combination with biologic DMARDs (bDMARDs) and/or adequate psychopharmacotherapy (PPT). To assess factors associated with MCI after five years.Materials and methods. 128 RA patients were enrolled, ADD were diagnosed in 123 (96.1%) by a licensed psychiatrist. Severity of depression and anxiety was evaluated with Montgomery – Asberg and Hamilton Anxiety scales. CI were diagnosed during clinical and psychological examination using the battery of pathopsychological and projective techniques. CI outcomes were considered favourable in cases with no CI diagnosed throughout the study and in cases of CI reversal. PPT was offered, 52 (42.3%) agreed. Patients were divided into the following treatment groups: сsDMARDs (n=39), сsDMARDs + PPT (n=43), сsDMARDs + bDMARDs (n=32), сsDMARDs + bDMARDs + PPT (n=9). Multivariable logistic regression was performed to determine factors associated with CI after five years.Results. MCI were diagnosed in a majority of RA patients (73.2%) including logical thinking impairments (51.2%) and memory deficit (67.5%). At 5-years endpoint 74 patients were included. Total CI rates in no-PPT groups increased from 69 to 85.7% (p=0.037) and were higher compared to PPT groups (85.7% vs 62.5%; р=0.021; RR=1.37). Patients with favourable CI outcomes had lower major depression prevalence and baseline Montgomery – Asberg scores, major improvement in depression symptoms and higher rates of ADD remission after five years. Baseline DAS28 (OR=1.29; р<0.001) was positively associated and remission of ADD negatively associated with MCI after five years (OR=0.25; р=0.03), R2=0.48; p<0.001.Conclusion. ADD and MCI are highly prevalent in RA patients. While CI tend to persist and worsen over time, PPT is associated with reduced risk of CI in long-term perspective. Personalized PPT with antidepressants and neuroleptics may show potential to lessen the rates of MCI in RA patients with ADD.